Technology venture blueprint Cartsmarter Enterprise Sdn Bhd “GPSCART” / Amirah Syahirah Sukran - Sukran, Amirah Syahirah (2020)
CartSmarter Enterprise is manufacturer of shopping cart, thus we would like to supply our product, GPSCart to all supermarkets, hypermarkets, grocery stores and another departmental stores. The cart provides high quality of cart with uniquedesign and features at value pricing that affordable for our target market such as Tesco, AEON, Giant, Mydin, Maslee, Econsave, KipMart and Target. Furthermore, this cart is a smart navigation shopping cart that is different from other existing shopping cart. There were many added features have been proposed to produce this new product such as it is completed with navigation system and security system. Therefore, this situation provides good opportunities for us to expand our business and gain moreprofit by proper manipulating thissituation.Furthermore,CartSmarter offer perfect after-sales guidance which we will give a complete installation guidance and three years warranty against rust and corrosion with our coating process.